FAKTOR-FAKTOR YANG MEMPENGARUHI OPTIMIZATION ENERGY SAVING IN LARGE AIRPORT TERMINAL: HVAC TECHNOLOGY, ECO AIRPORT SYSTEM DAN ENERGY MANAGEMENT AND CONTROL - Arinda, Nabilah Hasna; Syahra Putra, Anas; Amalia, Direstu; Martadinata, M. Indra; Sunardi, Sunardi (Politeknik Penerbangan Surabaya, 2024)
The increasing operation of airports makes these public areas generate high energy consumption. There have been many previous studies that discuss innovations in order to save energy use in different commercial buildings, such as offices and housing. Not only that, these literature studies discuss the use of different factors in each trial. Therefore, this paper aims to build a hypothesis of the influence of each variable used in future relevant research so as to strengthen the theory being discussed. For the types of variables in this study, a literature study on the concept of eco airport, will use factors that affect the optimisation of energy saving in large airport terminals, namely HVAC technology, eco airport system and energy management and control. The purpose of this paper is to discuss the influence of HVAC technology, eco airport system and energy management and control as development factors that influence optimisation energy saving in large airport terminals. Previous relevant research is very important to be used in making this research. The existence of this, makes this literature review article has the final result that HVAC technology affects the optimisation of energy saving in large airport terminals, eco airport system affects the optimisation of energy saving in large airport terminals, and energy management and control affects the optimisation of energy saving in large airport terminals. Keywords: Optimization Energy Saving in Large Airport Terminal; HVAC Technology; Eco Airport System; Energy Management and Control